2020
DOI: 10.1097/brs.0000000000003602
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscopic Observation of Myodural Bridge in the Human Suboccipital Region

Abstract: Study Design. A scanning electron microscopic study performed on three cadaveric specimens focused on the human suboccipital region, specifically, myodural bridge (MDB). Objective. This study showed the connection form of the MDB among the suboccipital muscles, the posterior atlanto-occipital membrane (PAOM) and the spinal dura mater (SDM), and provided an ultrastructural morphological basis for the functional studies of the MDB. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…In previous studies [14,28], scanning electron microscopy (SEM) and histological investigations observed that some of the MDB fibers originated from the ventral part of the RCPmi muscle. These fibers passed through the atlanto-occipital interspace and gradually merged into the SDM forming the superficial layer of the SDM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies [14,28], scanning electron microscopy (SEM) and histological investigations observed that some of the MDB fibers originated from the ventral part of the RCPmi muscle. These fibers passed through the atlanto-occipital interspace and gradually merged into the SDM forming the superficial layer of the SDM.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the surgical treatment of CM primarily involves bone decompression, duraplasty, the resection of the tonsils of the cerebellum, and other methods [4,11,12,22,31]. These cervical surgical procedures often result in postoperative complications such as cerebrospinal fluid leakage, pseudomeningocele, hemorrhage, and reduced dural tension, due to occipital periosteum dissection, MDB removion, and improper dural dissection [9,14,18,19,24]. Therefore, we propose that during surgery, attention should be paid to the protection of the three sources of fibers of composing the spinal dura mater.…”
Section: Discussionmentioning
confidence: 99%
“…The material surrounding blood vessels and lymphatics includes interstitial connective tissue (31). The myodural bridge connects the rectus capitis posterior with the dura (133,134) and there is evidence that the meninges and the brain function as one network (135)(136)(137)(138). Modulating interstitial connective tissue would cause biomechanical, vasomotor and neuromodulatory effects (31).…”
Section: The Problem With Dry Needling In Light Of Bio-tensegritymentioning
confidence: 99%
“…Zheng et al proposed that the MDB originating from the suboccipital muscles formed a functional unit that they termed the 'Myodural Bridge Complex' (MDBC) 12 . Jiang et al described the ultra-microstructure of the human MDB via scanning electron microscopy 13 .…”
Section: Introductionmentioning
confidence: 99%